Multiple minima hypersurfaces procedures for biomimetic ligands screening - Mascini, M. (2011)
In this work the interaction of the pesticide carbaryl with two groups of biomimetic ligands, peptides and MIPs was screened by multiple minima hypersurfaces (MMH) procedures, through the AM1 semiempirical method. Data related to the properties of the molecular association of the complex biomimetic ligand-pesticide were obtained and compared with another molecular modeling algorithm named Leapfrog, as included in the Sybyl software package, and experimental results from the literature, remarking good correlation between them. All important MMH program parameters (cells number, box size, conformers) were studied and optimized with the aim of getting the minimum computation time without losing the correlation with experimental data. The data demonstrated that MMH approach can be used as a fast biomimetic ligand screening tool for MIPs. In the case of peptides the computation time was not comparable with the molecular dynamics methods conventionally used for this approach. © 2011 Springer Science+Business Media B.V.